Екосистемний підхід до оцінки збитків, завданих воєнними діями - Дідух, Я.П. (Вісник НАН України, 2022)
У статті висвітлено екологічні аспекти оцінки збитків, завданих довкіллю внаслідок повномасштабного вторгнення РФ в Україну. Запропоновано оцінювати збитки в балах за трьома критеріями: ступінь пошкодження,
стійкість та вразливість на прикладі урбоекосистем. Автор наголошує,
що зволікання з вирішенням екологічних проблем у найближчому майбутньому може призвести до значно більших екологічних та економічних наслідків, ніж ми уявляємо на початковому етапі. Ключове завдання для
екологів полягає в тому, щоб передбачити «каскадні процеси», оцінити їх
можливий негативний вплив на довкілля і запропонувати ефективні заходи
протидії. Підкреслено, що заходи з відновлення довкілля потребують розроблення комплексних програм, залучення наукових, людських і технічних ресурсів, пошуку джерел фінансування, зокрема відшкодування збитків за рахунок коштів агресора. The ecological aspects of the assessment of damage to the environment and living conditions caused by destructions due
to the full-scale military invasion of Ukraine by the Russian Federation in 2022, related to various spheres of public life
and the nature of Ukraine, are covered in the article. It is proposed to estimate losses in points according to three criteria:
damage (destruction), resilience, and vulnerability of ecosystems. The urban ecosystem, which includes a complex of
buildings and infrastructure (technotopes) and natural vegetation areas, is taken as a basis. It is proposed to rate on a
four-point scale the features that characterize the damage to the urban ecosystem, its resilience, and vulnerability. The
possibilities of the restoration of all urban ecosystems are divided into five categories depending on the scales and sizes,
and degree of losses. This separation is the basis for a more detailed assessment of the loss of ecosystem services, size,
mechanisms, and sources of compensation. Problems of direct destruction and damage to natural types of ecosystems
(biotopes) and possible consequences that may be even more destructive and manifest over a long period of time are analyzed.
Among such consequences are the damage from fires; the impact on the atmosphere and climate; the increase in
background radiation level; the pollution of the sea and inland waters; the disturbance of soils and land surface; the loss
of function and transformation of ecosystems, reduction of ecosystem services; the devastation of protected areas and loss
of their value; the spread of alien species, pests, pathogens and extinction of the most vulnerable natural species, i.e. reduction
of biodiversity. Overcoming the consequences requires the development of comprehensive programs, involvement
of scientific, human and technical resources, which requires finding sponsors, the sources of assistance and compensation
at the expense of the aggressor.